Decreasing prevalence of social drinkers in Australia. (April 2017) - Callinan, Sarah; Pennay, Amy; Livingston, Michael
Abstract: Introduction: There has been a recent decrease in population level alcohol consumption in Australia, particularly in young people. Whether this is due to increasing abstinence or a shift in the way people think about alcohol is not known. The aim of this study is to investigate trends in self-identification of drinker types in Australia from 2001 to 2013 in light of shifting patterns of alcohol consumption in Australia. Methods: Five waves of the National Drug Strategy Household Survey from 2001 to 2013 (N = 118, 416) were used to assess trends in self-identification as a drinker type (non-, ex-, occasional, light, social, heavy and binge drinker). Consumption patterns and demographics of the self-identified groups were also examined. Results: The pattern of self-identification has mostly remained steady over time. The two exceptions to this are a decrease in identification as a social drinker (28% to 22%) and a corresponding increase in identification as a non-drinker (from 19% to 27%). There are few changes over time in the demographic make-up of, or consumption patterns in, the social drinker category with the exception of those over 50, who continue to identify as social drinkers at the same rate. Conclusion: The recent increase in abstinence in Australia seems to be matched by a corresponding decrease in self-identified social drinkers, particularly among those under 50. This indicates that the decrease in consumption is not occurring in those most likely to experience harms. Highlights: The proportion of people who considered themselves to be a social drinker decreased from 28% to 22%. There was an increase in the proportion of those described themselves as a non-drinker; 19% to 27%. The drinking habits of those who self-identify as each drinker type have not changed over time. This shift was not found in those respondents aged 50 and over.